Are correlations between deadwood fungal community structure, wood physico-chemical properties and lignin-modifying enzymes stable across different geographical regions?. (August 2016) - Purahong, Witoon; Arnstadt, Tobias; Kahl, Tiemo; Bauhus, Jürgen; Kellner, Harald; Hofrichter, Martin; Krüger, Dirk; Buscot, François; Hoppe, Björn
Abstract: Wood-inhabiting fungi are major agents of wood decomposition. However, it is unclear which factors determine their distribution and enzyme production. Many studies that have addressed this issue suffer from a lack of geographic extent. Here, we investigate the fungal community structure of 117 Fagus sylvatica logs in relation to wood physico-chemical properties and secreted ligninolytic enzymes, across three distinct geographical regions of Germany. Our results revealed that fungal community structure was similar across different regions, but was nevertheless variable in all regions. The relationships between fungal community structure, wood physico-chemical properties and enzyme activities were not consistent across different regions. However, we identified that the wood physico-chemical properties (i.e. decay class, remaining mass, density, extractives, total lignin and pH) were the most important factors associated with the fungal community structure in all three regions. In contrast, the wood physico-chemical properties and the fungal community structure did not sufficiently explain variation in the detected enzymatic activities. Thus, we assume that interspecific interactions and recently described priority effects play more important roles in the production of lignin modifying enzymes. Highlights: We identified factors corresponding to fungal community structure across different geographical regions in Germany. Correlations between fungal community and lignin-modifying enzymes were not consistent across all regions. Interspecific interactions and priority effects may explain activities of lignin-modifying enzymes.